Staphylococcus argenteus from rabbits in Thailand. Issue 4 (21st June 2018) - Indrawattana, Nitaya; Pumipuntu, Natapol; Suriyakhun, Nawarat; Jangsangthong, Arunee; Kulpeanprasit, Suphang; Chantratita, Narisara; Sookrung, Nitat; Chaicumpa, Wanpen; Buranasinsup, Shutipen
Abstract: Staphylococcus argenteus, a novel species of the genus Staphylococcus or a member of the S. aureus complex, is closely related to S. aureus and is usually misidentified. In this study, the presence of S. argenteus in isolated S. aureus was investigated in 67 rabbits with abscess lesions during 2014–2016. Among 19 S. aureus complex isolates, three were confirmed to be S. argenteus by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry, nonribosomal peptide synthetase gene amplification, and multilocus sequence type. All S. aureus complex isolates, including the S. aureus isolates, were examined for their antimicrobial resistance phenotype by disk diffusion and for their resistance genotype by PCR assays. Among the S. argenteus isolates, one was susceptible to all antimicrobial drugs and the other two were resistant to penicillin and doxycycline. In contrast, most S. aureus isolates were resistant to penicillin (37.5%), and gentamicin (12.5%). Moreover, S. aureus isolates harbored the bla Z, mec A, aac A ‐aph D, and mrs (A) as well as mutations of gyr A and grl A, but S. argenteus isolates carried solely the bla Z. S. argenteus isolates were investigated for enterotoxin ( sea ‐ sed ) and virulence genes by PCR. One isolate carried sea, sec, and sed, whereas the other two isolates carried only sea or sed . No isolate carried seb and see . All three S. argenteus isolates carried hla, hlb, and clf A, followed by pvl, whereas coa, spa (IgG‐binding region), and spa (x region) were not detected in the three isolates. This paper presents the first identification of S. argenteus from rabbits in Thailand. S. argenteus might be pathogenic because the isolates carried virulence genes. Moreover, antimicrobial resistance was observed. Investigations of this new bacterial species should be conducted in other animal species as well as in humans. Abstract : Staphylococcus argenteus, a novel species of the genus Staphylococcus, is usually misidentified with S. aureus and can be differentiated only by the molecular technique. This is the first time that S. argenteus has been identified from the rabbit in Thailand.